Navigating Human Capital Challenges: Understanding the Decline in White Members of the South African Navy - Kubu, Asiel E.; Pillay, Strinivasan S. (Scientia militaria : South African journal of military studies, 2025)
The concept “human capital” refers to 'the accumulation of competencies, knowledge and skills needed to perform a task' as defined by John C Groth and Gregory M Hebb.2 This implies that, to a degree, the effectiveness of an organisation depends on the quality and effectiveness of its employees. The Republic of South Africa is a sovereign democratic state founded on the values of human dignity, the achievement of equality, and the advancement of human rights.3 As part of the public sector, the Department of Defence is expected to transform in order to ensure inclusiveness of all race groups. The objective of the South African National Defence Force Human Resource Strategy 2010 is to ensure compliance with the overall government intent of transformation. This strategy aims to establish an 'efficient, effective and economical human resource composition of the right quality and quantity' for the Department of Defence.4 In line with the South African National Defence Force Human Resource Strategy 2010, the South African Navy pursued recruitment interventions favouring the appointment of black personnel in order to address inequalities of the past in terms of demographics. This led to fewer white youth being inducted, resulting in a predominantly black South African Navy. To investigate this challenge, the current study adopted mixed research approach (qualitative and quantitative). The qualitative research comprised a literature review on human capital, the transformation process in the South African National Defence Force, the demographics of the country, and interviews with serving white recruits in the South African Navy. Furthermore, a questionnaire survey (quantitative research) targeting white youth was administered in Gauteng, a province in South Africa, to obtain data.